Interrogating Membrane Protein Conformational Dynamics within Native Lipid Compositions. Issue 49 (8th November 2017) - Reading, Eamonn; Hall, Zoe; Martens, Chloe; Haghighi, Tabasom; Findlay, Heather; Ahdash, Zainab; Politis, Argyris; Booth, Paula J.
Abstract: The interplay between membrane proteins and the lipids of the membrane is important for cellular function, however, tools enabling the interrogation of protein dynamics within native lipid environments are scarce and often invasive. We show that the styrene–maleic acid lipid particle (SMALP) technology can be coupled with hydrogen–deuterium exchange mass spectrometry (HDX‐MS) to investigate membrane protein conformational dynamics within native lipid bilayers. We demonstrate changes in accessibility and dynamics of the rhomboid protease GlpG, captured within three different native lipid compositions, and identify protein regions sensitive to changes in the native lipid environment. Our results illuminate the value of this approach for distinguishing the putative role(s) of the native lipid composition in modulating membrane protein conformational dynamics. Abstract : Going native : Membrane proteins function within cellular membranes, which are composed of diverse arrays of lipids. By coupling native nanodisc technology with hydrogen–deuterium exchange mass spectrometry, an approach was developed for interrogating the conformational dynamics of a membrane protein (green) within complex native lipid environments.